THE MODERN VISION ON THE SYSTEM OF ASSESMENT OF THE MORALPSYCHOLOGICAL STATE OF PERSONNEL - Aleshchenko, V.; Neval`onij, E. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article covers the issue of assessment of the moral-psychological state of personnel of the military units of the Armed Forces of Ukraine, within the framework of a general system of moral psychological support to the activity of troops (forces). It has been stipulated that the system of assessment has not been sufficiently developed in terms of modern military theory and practices. The modern new approach is defined by scrutinizing the issue under research as a complex social system of military purpose. The main of its elements are under analyses considering the experience of the Armies of countries that are NATO-members. It is mentioned that the main subjects of the system of assessment of the moral-psychological state of personnel are the commanders (chiefs) and officers of the structures of moral-psychological support. Based on the analyses of different approaches towards the research of the moral-psychological state, it has been determined that the moral psychological state of personnel – as a complex of ongoing psychological possibilities of military personnel and military teams, aimed at solving a particular task which is the most important object of the system. The existing methods of assessment of the moral-psychological state of personnel which have been under research are based on traditional methods of informational gathering and require simplification and automatization for a qualitive processing and interpretation of results. The necessity to improve the main elements of the system of assessment of the moral-psychological state of personnel of military units of the Armed Forces of Ukraine in the course of training and carrying out tasks in accordance with their purpose and its further adaptation to the standards of NATO military command has been pointed out. It has been determined, that the effective functioning of the system of assessment of the moral-psychological state is to assure the timely gathering, generalization and interpreting of data regarding to the moral readiness and psychological capability of the personnel of military units of the Armed Forces of Ukraine to perform combat tasks as such to be included in the course taking decisions of command and control. There are argumented recommendations provided on the improvement of the system of assessment of the moralpsychological state of the military units of the Armed Forces of Ukraine.